Transdiagnostic Treatment Personalization: The Feasibility of Ordering Unified Protocol Modules According to Patient Strengths and Weaknesses. Issue 4 (July 2019) - Sauer-Zavala, Shannon; Cassiello-Robbins, Clair; Ametaj, Amantia A.; Wilner, Julianne G.; Pagan, Danyelle
Most patients in community practice attend significantly fewer sessions than are recommended by treatment protocols that have demonstrated efficacy in addressing emotional disorders. Personalized interventions that target the core processes thought to maintain a wide range of disorders may serve to increase treatment efficiency, addressing this gap. This study sought to evaluate the feasibility and acceptability of the personalized delivery of a mechanistically transdiagnostic intervention, the Unified Protocol (UP) for Transdiagnostic Treatment of Emotional Disorders. Using an AB phase change design in accordance with the single-case reporting guideline for behavioral interventions (SCRIBE), 18 individuals with heterogeneous emotional disorders were randomly assigned to receive UP treatment modules ordered according to either their pretreatment strengths or weaknesses. Results support the feasibility of reordering the treatment modules as the majority of patients presented with marked differences in skill levels, as well as the acceptability of this approach as patients in both conditions reported satisfaction with their assigned treatment order. Furthermore, the majority of patients demonstrated symptom improvement consistent with previously reported effects of the standard-order UP. Finally, there is preliminary evidence to suggest that those in the strengths condition displayed improvements in outcomes earlier in treatment than those in the weaknesses condition. Taken together, these findings offer preliminary support for improving treatment efficiency through the utilization of a personalized, strengths-based, transdiagnostic approach.